Religious Festival Celebrations in a Multicultural Context: A Case Study of Eid al-Fitr at the Niujie Mosque in Beijing, China - Abdullah Mufid Mubarrok; Zahwa, Muhammad Faisol; Iskandar, Mohammad Fajar; Siregar, Wahidah Zein Br (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This paper examines the dynamics of Eid al-Fitr celebrations at the Niujie Mosque in Beijing as a representation of the lived experiences of multiethnic Muslim communities in China. Employing a descriptive qualitative approach and case study methodology, the research highlights how Muslims from diverse ethnic backgrounds—such as Hui, Uighur, and Kazakh interact and engage in cultural integration while celebrating Islamic traditions amid the dominance of Chinese culture and a tightly controlled political system. As the oldest mosque in Beijing, the Niujie Mosque serves not only as a spiritual center but also as a symbol of harmony between Islamic teachings and local traditions. The Eid celebration here functions as a religious occasion as well as a site of social interaction, cultural diplomacy, and identity negotiation. The findings reveal that the Muslim community in Beijing maintains its religious identity through adaptive acculturative practices, such as incorporating local architecture, serving halal Chinese dishes, and involving multiple ethnic groups in religious activities. These findings affirm that Islam in China is not monolithic but rather flourishes in diversity and blends organically with local culture.